Basic statistics and pharmaceutical statistical applications - De Muth, James E (CRC Press Pharmacy Education Series, 2014)
"This book serves as an introduction to statistics for undergraduate and graduate students in pharmacy as well as a reference guide for professionals in various pharmacy settings. Designed specifically for non-statisticians, the text avoids heavy mathematics and concentrates on the practical application of the most commonly employed statistical tests. This edition introduces new statistical tests and includes Excel and Minitab applications for descriptive and inferential statistics"--